Description of the second- and third-instar larva of South African Stenomastigus longicornis (Boheman) (Coleoptera: Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł; Kilian, Aleksandra (Zootaxa, 2016)
The second- and third-instar larvae of the South African species of Mastigini, Stenomastigus longicornis, are described. The serial homology of chaetotaxic structures and differences between larval instars are discussed. The larva of Stenomastigus is very similar to that of Palaeostigus, but differences in proportions of body parts, number of setae on the head, thorax and abdomen and possibly also the shape of the antennal sensory appendage can be used to distinguish them. A frontal impression surrounded by modified setae with greatly enlarged surface, presumably functioning as a glandular evaporation apparatus, and the antennomere II subdivided into three sections, are suggested as synapomorphies of Mastigini; within Mastigitae this tribe is also unique in lacking the urogomphs, which are present in larvae of Leptomastacini and Clidicini. Geniculate and slender antennae with a strongly oblique distal margin of antennomere II are a putative larval synapomorphy of Mastigitae.